2013
DOI: 10.4049/jimmunol.1202282
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Tumor-Associated MicroRNAs Modulate the Survival and Longevity of Dendritic Cells by Targeting YWHAZ and Bcl2 Signaling Pathways

Abstract: Tumors use a wide array of immunosuppressive strategies, such as reducing the longevity and survival of dendritic cells (DCs), to diminish immune responses and limit the effect of immunotherapy. In this study, we found that tumors upregulate the expression of multiple microRNAs (miRNAs), such as miR-16-1, miR-22, miR-155, and miR-503. These tumor-associated miRNAs influenced the survival and longevity of DCs by affecting the expression of multiple molecules that are associated with apoptotic signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 46 publications
2
36
0
Order By: Relevance
“…It's also reported that at least some kinds of tumor have developed the ability to influence the endogenous level of miR15a/16 in immune cells, thus to ameliorate antitumor immune response. Siping et al [23] found when co-cultured with melanoma cell-line B16, miR-16 level of bone marrow-derived dendritic cells was upregulated, through which way tumor cells promoted apoptosis of DCs. This phenomenon suggests that maybe tumor can restrict antitumor immune response by regulating the miRNA level of immune cells.…”
Section: Mir-15a/16 Function As Modulators Of Immune Responsementioning
confidence: 98%
See 1 more Smart Citation
“…It's also reported that at least some kinds of tumor have developed the ability to influence the endogenous level of miR15a/16 in immune cells, thus to ameliorate antitumor immune response. Siping et al [23] found when co-cultured with melanoma cell-line B16, miR-16 level of bone marrow-derived dendritic cells was upregulated, through which way tumor cells promoted apoptosis of DCs. This phenomenon suggests that maybe tumor can restrict antitumor immune response by regulating the miRNA level of immune cells.…”
Section: Mir-15a/16 Function As Modulators Of Immune Responsementioning
confidence: 98%
“…There have been researches aimed at enhancing chemosensitivity of tumor by upregulating miR-15a/16. These two miRNAs are also reported to regulate angiogenesis [16,17] and immune response [18][19][20][21][22][23]. What's puzzling is that miR-15a/16 were also found to be upregulated in some types of cancer, indicating their potential roles as oncomiRs.…”
mentioning
confidence: 93%
“…In the presence of tumor cells DCs undergo apoptosis at higher rates compared to DCs that were co-cultured with normal fibroblasts. Furthermore, it was observed that these miRNAs specifically targeted PI3K/AKT, MAPK and apoptotic signaling pathways in DCs (53). …”
Section: Tumor-infiltrating Dcsmentioning
confidence: 99%
“…Western Blotting was performed as described previously [12]. Hybridiz ations with primary antibodies were carried out for one hour at room temperat ure in blocking buffer.…”
Section: Western Blotting Analysismentioning
confidence: 99%